Community Pharmacists’ Perceptions on Ethical Dilemmas, Pharmacy Values and Decision-making - Rajiah, Kingston; Venkataraman, Rajesh (Indian Journal of Pharmacy Practice)
Background: Ethics can be predisposed by an individual’s values, education, social activities, professional activities, belief, and individual’s need. Objective: This study was designed to find out the dilemma in handling ethical issues at community pharmacy settings; to find out the frequency of ethical dilemma at community pharmacy settings; to find out the reasons why community pharmacists may compromise ethical values; to find out how frequent the community pharmacists are involved in ethical dilemma situations. Methods: A descriptive, cross-sectional study was conducted using a validated self-administered questionnaire from March 2016 to December 2017. The participants were selected using a multi-stage cluster random sampling. Results: In this study, 1057 community pharmacists were approached to participate in this study. Out of this, 742 community pharmacists responded by completing the questionnaire. The response rate in this study is 70.19%. More than half of the issues given were measured as “difficult” and “very difficult” by the community pharmacists. The most common ethical dilemma was fear of breaking trustworthiness which strongly impacts the pharmacist–physician collaborations. ‘Carry out patient’s request’ ‘physician’s orders’ and ‘employer`s request’ were the reasons of community pharmacists compromising the ethical values. Conclusion: Community pharmacists are confronted with numerous ethical problems in their daily work. Most of the pharmacists face the ethical dilemma situations at least once a week in their pharmacies. Community pharmacists compromise on their values and ethical issues not only because of patient’s or physician’s request but also because of their employers’ intrusion.
Keywords: Community pharmacy; Ethic; Decision-making; India; Pharmacy value.